The Relationship Between Entrepreneurial Intention and Action: The Effects of Fear of Failure and Role Model - Kong, Fanzhu; Zhao, Lily; Tsai, Cheng-Hung (Frontiers in Psychology, 2020)
The purpose of the study was to examine the moderating effect of business role model and fear of failure on the relationship between entrepreneurial intention and behavior. The participants were sampled from 1865 college students who graduated from universities in China from 2012 to 2018. The experimental instrument was comprised of 4 scales concerning entrepreneurial intention, entrepreneurial behavior, fear of failure, and business role model. The data were analyzed using hierarchical regression. The results showed that: (1) Entrepreneurial intention was positively influenced the entrepreneurial behavior; (2) Fear of failure weakened the relationship between entrepreneurial intention and action; (3) The moderating effect of business role model on entrepreneurial intention and behavior was confirmed. We concluded that entrepreneurial intention was positively related to the entrepreneurial behavior, fear of failure hindered college students from taking entrepreneurial behavior, and business role model will enhance their entrepreneurial intention. The paper suggest that some measures should be taken to overcome college students’ fear of failure, and to improve the education system of entrepreneurship in order to cultivate talents with creativity.